2016
DOI: 10.15406/japlr.2016.03.00046
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bacteriostatic and Bactericidal Activities of Senna alata, Ricinus communis and Lannea barteri extracts Against Wound and Skin Disease Causing Bacteria

Abstract: Antibacterial activities of the extracts of three medicinal plants, Senna alata, Ricinus communis and Lannea barteri from two different extractants were studied. Bacteria strains such as Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumoniae and Escherichia coli are known wound and skin disease causing bacteria. For 100g of each plant material, the percentage yields of the extracts were determined and ranged between 5.20% and 12.40%. Phytochemical screening of the crude extracts of Senna alata, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Additionally, an outcome of synergism resulting from combination therapy is to minimize or delay the emergence of resistance by the pathogenic organism to the individual components of the combination [ 4 , 17 ]. The synergy and additive effects exhibited by the extract-extract interactions in the current work could be attributed to the different phyto-compounds in the individual extracts [ 5 , 6 ] acting in concert, each introducing a different mechanism to inhibit or kill the microbial growth.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Additionally, an outcome of synergism resulting from combination therapy is to minimize or delay the emergence of resistance by the pathogenic organism to the individual components of the combination [ 4 , 17 ]. The synergy and additive effects exhibited by the extract-extract interactions in the current work could be attributed to the different phyto-compounds in the individual extracts [ 5 , 6 ] acting in concert, each introducing a different mechanism to inhibit or kill the microbial growth.…”
Section: Resultsmentioning
confidence: 92%
“…Different extracts from the same plant were not considered. The MICs of the extracts acting alone were reported in a previous study conducted in our laboratory [ 5 , 6 ]. It was observed that MICs ranged between 3.13 and 25.00 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method described by Donkor et al [18] was used to determine the minimum fungicidal concentrations (MFCs). A commercial standard, Fluconazole (Sigma), was used as positive control (1-3000 μg/ml) and DMSO (99.9%) as negative control.…”
Section: Determination Of Minimum Fungicidal Concentration (Mfc)mentioning
confidence: 99%